Low temperature degradation - ageing of a zirconia dental implant - Miranda, Mónica (2022)
This work compares the topographical aspect of the surface and its chemical composition of a zirconia dental implant before and after artificial ageing. Two implants commercialized were analysed, both made from zirconia: Straumann ZLA Pure (TM) Ceramic. The chemical tests performed allowed to identify the elements of the implants' surface and the topographical test was used to observe the surface of the implants before and after ageing. Both tests provide information about the alterations occur on the surface of the implant after ageing.